Simultaneous determination of eight bioactive components of Qishen Yiqi dripping pills in rat plasma using UFLC–MS/MS and its application to a pharmacokinetic study. (9th April 2017) - Shao, Yaping; Zhang, Wen; Tong, Ling; Huang, Jingyi; Li, Dongxiang; Nie, Wei; Zhu, Yan; Li, Yunfei; Lu, Tao
Abstract: In this study, a rapid and reliable ultra‐fast liquid chromatography–tandem mass spectrometry method was developed and validated for the simultaneous determination of eight active ingredients, including astragaloside IV, ononin, tanshinol, protocatechualdehyde, protocatechuic acid, salvianolic acid D, rosmarinic acid and ginsenoside Rg1, in rat plasma. The plasma samples were pretreated by protein precipitation with acetonitrile. Chromatographic separation was performed on a Waters Acquity UPLC® BEH C18 column (1.7 μm particles, 2.1 × 100 mm). The mobile phase consisted of 0.1% aqueous formic acid (A)–acetonitrile with 0.1% formic acid (B) at a flow rate of 0.4 mL/min. Quantification was performed on a triple quadruple tandem mass spectrometry with electrospray ionization by multiple reaction monitoring both in the negative and in the positive ion mode. The lower limit of quantification of tanshinol was 2.0 ng/mL and the others were 5.0 ng/mL. The extraction recoveries, matrix effects, intra‐ and inter‐day precision and accuracy of eight tested components were all within acceptable limits. The validated method was successfully applied to the pharmacokinetic study of the eight active constituents after intragastric administration of three doses (1.0, 3.0, 6.0 g/kg body weight) of Qishen Yiqi Dripping Pills to rats.